2001
DOI: 10.1086/324427
|View full text |Cite
|
Sign up to set email alerts
|

Associations of CCR5, CCR2, and Stromal Cell–Derived Factor 1 Genotypes with Human Immunodeficiency Virus Disease Progression in Patients Receiving Nucleoside Therapy

Abstract: Genotype data for CCR5, CCR2, and stromal cell-derived factor 1 (SDF-1) were obtained from 354 human immunodeficiency virus type 1 (HIV-1)-positive subjects who were being treated with nucleosides. Associations with HIV-1 load, HIV syncytium-inducing (SI) phenotype, CD4 cell count, and disease progression were analyzed. No differences in HIV-1 load or CD4 cell count were observed between wild type (+) and variant genotypes. Changes from non-SI to SI viral phenotype were more frequent in heterozygotes with a 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
5
18
4
Order By: Relevance
“…Our results agree with the findings of Lathey et al [20] in that SDF1-3 ′ A genotype has no effect on HIV-1 load or CD4+ cell counts of patients under antiretroviral therapy.…”
Section: Sdf1-3 ′ a And Hiv-1 In Mexicanssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with the findings of Lathey et al [20] in that SDF1-3 ′ A genotype has no effect on HIV-1 load or CD4+ cell counts of patients under antiretroviral therapy.…”
Section: Sdf1-3 ′ a And Hiv-1 In Mexicanssupporting
confidence: 93%
“…The existence of HIV-1-infected patients homozygous for the Delta-32 allele [32,33] means that there are other coreceptors contributing to virus entry, like CXCR4, CCR1, CCR8, CCR2, and CCR3B [19,34,35] , despite the lack of CCR5. For this reason, at least in part, several studies have failed to correlate the SDF1-3 ′ A genotype to coreceptor usage [14,20,36] .…”
Section: Sdf1-3 ′ a And Hiv-1 In Mexicansmentioning
confidence: 99%
“…Although these results appear inconsistent, it may be that the genetic polymorphisms studied have more affect on the individual's ability to maintain suppression or virologic profile rather than on the initial suppression after HAART. For example, in a recent paper by Lathey et al [27], there was no difference in HIV-RNA suppression by genotype, but there was a difference in the distribution of syncitium-inducing virus by CCR5 ∆32 genotype among patients receiving nucleosides. There may be further genetic characteristics of the host that need to be taken into account when examining determinants of maintaining suppressed virus.…”
Section: Methodologic Challengesmentioning
confidence: 96%
“…A large metaanalysis [31], however, showed that the CD4 count at HAART initiation is a major prognostic factor for clinical response to HAART, in terms of AIDS and death; viral load at commencement was prognostic of subsequent clinical progression only if ! 100 000 copies/mL.In our cohort, the cell phenotypes in terms of expression of CCR5 and the viral genotypes of the circulating strains of the patients in terms of R5 or X4 were not available [32,33]. The pathophysiological mechanism underlying the better virological response in D32 heterozygotes remains unclear.…”
mentioning
confidence: 90%